Development Status and Countermeasures of Chinese Animation Films - Yan, Wenyu (International Journal of Global Economics and Management, 2024)
This paper studies the development status and countermeasures of Chinese animated movies. First, it introduces the definition and development history of Chinese animated films, including their characteristics and influence. Then, it analyzes the current industrial scale, content creation, audience groups, as well as the problems and challenges of Chinese animated films. Aiming at these problems, this paper puts forward a series of countermeasures and suggestions, including support and guidance at the policy level, collaborative development and innovation of the industry, improvement of the quality of content and creation level, talent cultivation and exchanges, as well as expanding the market and improving international influence.